Evidence of inflammasome activation and formation of monocyte-derived ASC specks in HIV-1 positive patients - Ahmad, Fareed (AIDS <London>, 2018)
Objective:The formation of large intracellular protein aggregates of the inflammasome adaptor protein ASC (apoptosis-associated speck-like protein containing a caspase-recruitment domain; also know as PYCARD) is a hallmark of inflammasome activation. ASC speck-forming cells release the highly proinf
Gesehen am 25.04.2019
DOI funktioniert nicht